Supply-Side Drug Policy, Polydrug Use, and the Economic Effects of Withdrawal Symptoms - Alexander Ahammer; Analisa Packham (Institute of Labor Economics (IZA), 2024)
Despite the fact that 30 percent of opioid overdoses also involve a benzodiazepine, there is little policy guidance on how to curb concurrent misuse and even less evidence on how changes to co-prescribing practices can affect patients' economic trajectories. In 2012, Austria restricted access to flunitrazepam, one of the most potent, and most heavily misused, benzodiazepines. We use linked individual-level data to identify opioid users and estimate the reform's impact on their health and labor market outcomes relative to a randomly selected comparison group of non-opioid users. Estimates indicate a 12.7 percent drop in employment, a 13.1 percent increase in unemployment insurance claims, and a 26.5 percent increase in overall healthcare expenditures. We provide suggestive evidence that these effects are due to incapacitating withdrawal symptoms, rather than substitution to other drugs, including heroin or alcohol.
Keywords: I38; I12; J18; 330; opioids; substance use disorder treatment; benzodiazepines